2012
DOI: 10.1519/jsc.0b013e31822e5967
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Nintendo Wii Fit Aerobics and Traditional Aerobic Exercise in Sedentary Young Adults

Abstract: Exergaming is becoming a popular recreational activity for young adults. The purpose was to compare the physiologic and psychological responses of college students playing Nintendo Wii Fit, an active video game console, vs. an equal duration of moderate-intensity brisk walking. Twenty-one healthy sedentary college-age students (mean age 23.2 ± 1.8 years) participated in a randomized, double cross-over study, which compared physiologic and psychological responses to 30 minutes of brisk walking exercise on a tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
2
9

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 11 publications
5
62
2
9
Order By: Relevance
“…Results showed that the exercises' mean intensity level was of 43, 4 ± 16.7% of reserve HR, with a 3.5 ± 0.96 METs and energy expenditure of 116.2 ± 40.9 kcal/session, indicating that virtual games should be considered as an alternative tool for improving physical fitness and health. This possibility has also been observed in other studies related to the interpretation of physiological demand promoted by Nintendo Wii games 11,12 . However, it is important to highlight that virtual activity alone should not replace an oriented training program.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Results showed that the exercises' mean intensity level was of 43, 4 ± 16.7% of reserve HR, with a 3.5 ± 0.96 METs and energy expenditure of 116.2 ± 40.9 kcal/session, indicating that virtual games should be considered as an alternative tool for improving physical fitness and health. This possibility has also been observed in other studies related to the interpretation of physiological demand promoted by Nintendo Wii games 11,12 . However, it is important to highlight that virtual activity alone should not replace an oriented training program.…”
Section: Discussionsupporting
confidence: 78%
“…Although acute cardiovascular responses have not yet been effectively described with the use of Nintendo Wii, it has been proposed that some Nintendo Wii games could facilitate the meeting of recommendations from the American College of Sports Medicine (ACSM) regarding the improvement and maintenance of cardiorespiratory fitness 11,12 . Miyachiet al…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Os games de tennis, yoga, golf, ski, baseball, boliche e corrida apareceram em cerca de 36% do total dos jogos estudados 4,13,14,20,[26][27][28] . 4,6,[13][14][15][16]30 .…”
Section: Artigos Encontradosunclassified
“…(7) Miscellaneous studies found that the AVG's increase effort allowing enhanced body dynamics, raising the heart rate and thereby increasing levels of physical activity. (8,9,10,11) In the market, you will find many AVG's, such as Xavix, Playstation Eye Toy, Nintendo Wii and Xbox 360…”
Section: Introductionmentioning
confidence: 99%